2009
DOI: 10.26719/2009.15.2.432
|View full text |Cite
|
Sign up to set email alerts
|

Water-pipe [narguile] smokers in Lebanon: a pilot study

Abstract: Fumeurs de narguilé (pipe à eau) au Liban : une étude pilote RÉSUMÉ Nous avons réalisé une étude comparative afin d'évaluer les caractéristiques démographiques et sociales des fumeurs de narguilé, le lien avec la consommation de cigarettes et les maladies respiratoires chroniques, et le type de dépendance de quatre groupes : des sujets fumant uniquement le narguilé, des sujets fumant uniquement des cigarettes, des sujets fumant les deux et des sujets ne fumant pas du tout. La consommation de cigarettes était s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
33
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 13 publications
(12 reference statements)
4
33
0
1
Order By: Relevance
“…In terms of their composition, the metrics range from seven to 68 items. Developmental strategies for the metrics varied widely, from the use of qualitative and formative methods gaining insight from tobacco users,4 16–18 to developmental strategies that prioritised consultation with experts,17 19–22 or the use of items from existing diagnostic tools 18 23 24. The use of biological measures for measurement development also varied, with some studies using carbon monoxide5 17 25 26 and salivary/urinary cotinine5 17 18 26 to validate the soundness of their metric.…”
Section: Resultsmentioning
confidence: 99%
“…In terms of their composition, the metrics range from seven to 68 items. Developmental strategies for the metrics varied widely, from the use of qualitative and formative methods gaining insight from tobacco users,4 16–18 to developmental strategies that prioritised consultation with experts,17 19–22 or the use of items from existing diagnostic tools 18 23 24. The use of biological measures for measurement development also varied, with some studies using carbon monoxide5 17 25 26 and salivary/urinary cotinine5 17 18 26 to validate the soundness of their metric.…”
Section: Resultsmentioning
confidence: 99%
“…Inclusive, foi maior no sexo feminino do que no sexo masculino (16,66% e 14,28%, respectivamente) e também astronomicamente maior do que a prevalência nacional (aproximadamente 0,8%), tal como já foi observado em outras pesquisas, principalmente na população jovem 6, [29][30][31] . Nas últimas décadas, houve uma forte disseminação do uso do narguilé no Brasil, acompanhando o crescimento em outros países.…”
Section: Discussão E Conclusãounclassified
“…2 Elsewhere it has been shown that there is a strong doserelationship between shisha smoke exposure and prevalence of chronic bronchitis. 3 In Chinese water-pipe smokers (a variant on the Middle-Eastern pipe where the tobacco is lit directly instead of using coals) the rate of radiologically diagnosed emphysema was higher than in cigarette smokers or nonsmokers. 4 These clinical data are supported by animal models: chronic airway inflammation with eventual airflow limitation typical of COPD has been demonstrated using water-pipe smoke in mice.…”
Section: A Review Of the Health Effects Of Smoking Shishamentioning
confidence: 99%